Posttraumatic Stress Disorder: Bio-Psycho-Social Aspects, Eye Movement Desensitisation and Reprocessing and Autogenic Training in Persistent Stress: Case Study, Part 2 - Hašto, Jozef; Vojtová, Hana (European Journal of Mental Health, 2013)
In our case study, we illustrate the use of Eye Movement Desensitisation and Reprocessing (EMDR) and Autogenic Training (AT) in PTSD treatment. EMDR was used to manage the acute symptoms, while AT was used to enhance the resilience in persisting stress. Using the bio-psycho-social model of mental illness, we discuss the socio-political and socio-psychological aspects of this case that has put a burden on the relationship of two neighboring nations (Slovakia and Hungary) as well as on the relationship of the national majority and a minority within our country (Slovakia). Our patient consented to this report being published, and we hope that it will contribute to a more realistic evaluation of this event in society.